PENGARUH BUDAYA ORGANISASI, KOMPENSASI NON FINANSIAL DAN JOB INSECURITY TERHADAP TURNOVER INTENTION PT. PARIT PADANG PEKANBARU - Benny Saputra; Dewita Suryati Ningsih; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT Parit Padang Pekanbaru in order to determine the effect of variable Cultural Organization, Compensation and Job Insecurity Nonfinancial simultaneously on Turnover Intention in PT Parit Padang Pekanbaru. This study uses primary data obtained from interviews and giving questionnaires to all employees of PT Parit Padang Pekanbaru. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employees that numbered 43 people and sampled. The analytical method used in this study is the linear regression method berganda.Dari results of testing that was done, simultaneous regression test (Test-F) showed that the variables of Organizational Culture, Compensation and Job Insecurity Nonfinancial simultaneously significant effect on Turnover Intention. From the results of the partial test (t-test) showed that the variables of Organizational Culture, Compensation and Job Insecurity Nonfinancial significant effect on Turnover Intention. The result of the calculation of the coefficient of determination (R2) is equal to 0.794, which means, variable Organizational Culture, Compensation and Job Insecurity Nonfinancial together affect the Turnover Intention, while the rest influenced by other variables not examined in this study.Keyword: Organizational Culture, Compensation Non financial, Job Insecurity and Turnover Intention